2018
DOI: 10.1007/s12098-018-2791-0
|View full text |Cite
|
Sign up to set email alerts
|

Schmid Type Metaphyseal Chondrodysplasia with a Novel COL10A1 Mutation

Abstract: Schmid type metaphyseal chondrodysplasia (SMCD) is a rare skeletal dysplasia, characterized by short stature, short limbs, bowing of the legs, and radiographic features of metaphyseal irregularities with fraying and splaying, more severe at the knee. It is caused by mutations of the COL10A1 gene. The authors present an Indian patient with a novel COL10A1 gene mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Following the initial report of the COL10A1 gene mutation in SMCD [Mäkitie et al, 2005], at least 48 different heterozygous COL10A1 mutations have been reported in families with SMCD of different ethnic origin [Higuchi et al, 2016]. To date, the majority of mutations occur within the C-terminal NC1 domain [Mäkitie et al, 2005;Park et al, 2015;Higuchi et al, 2016;Goyal et al, 2018], which contains motifs that promote trimerization of the α1(X) chains and subsequent formation of the triple helix to yield stable collagen X molecules [Higuchi et al, 2016;Goyal et al, 2018]. Missense, nonsense, and frameshift mutations have been reported in the NC1 domain, and in 53% of the cases, premature termination codons resulting from nonsense and frameshift mutations have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the initial report of the COL10A1 gene mutation in SMCD [Mäkitie et al, 2005], at least 48 different heterozygous COL10A1 mutations have been reported in families with SMCD of different ethnic origin [Higuchi et al, 2016]. To date, the majority of mutations occur within the C-terminal NC1 domain [Mäkitie et al, 2005;Park et al, 2015;Higuchi et al, 2016;Goyal et al, 2018], which contains motifs that promote trimerization of the α1(X) chains and subsequent formation of the triple helix to yield stable collagen X molecules [Higuchi et al, 2016;Goyal et al, 2018]. Missense, nonsense, and frameshift mutations have been reported in the NC1 domain, and in 53% of the cases, premature termination codons resulting from nonsense and frameshift mutations have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several frameshift mutations have been reported in the COL10A1 gene and affected patients present with a similar phenotype as seen in our case, including short stature, waddling gate, metaphyseal irregularities, and coxa vara. However, the phenotype severity and others findings such as hyperlordosis showed both inter-and intrafamilial variability [Mäikitie et al, 2005;Woelfle et al, 2011;Park et al, 2015;Higuchi et al, 2016;Goyal et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…All of the identified mutation sites of COL10A1 associated with MCDS, including mutations in the present study, are located in the NC1 domain [4,8,12,22,23,24,25,26,27,28], except for two missense mutations in the signal peptide and one in the triple helical domain.…”
Section: Discussionmentioning
confidence: 50%
“…To the best of our knowledge, this is the first report of MDSC associated with factor VII deficiency worldwide. There have been reports of MDSC from other regions, including India (three-year old girl), Venezuela (eight-year-old girl), and Japan (three-year-old boy) [1,6,10]. A cohort study done by Makitie et al included 10 patients with confirmed MDSC, who were subsequently followed over time [11].…”
Section: Discussionmentioning
confidence: 99%
“…Metaphyseal chondrodysplasia, Schmid type (MDSC) is a rare autosomal dominant condition caused by a mutation in the COL10A1 gene [1]. It manifests in early childhood and results in a wide range of skeletal deformities.…”
Section: Introductionmentioning
confidence: 99%